Penggunaan IoT untuk Meningkatkan Kualitas Smart Home Pada Era Industri 4.0 - Rahmad, Iwan Fitrianto; Fragastia, Vidi Agung; Doni, Rahmad; Ginting, Ria Ukur; Pasaribu, Jamil (LPPM Universitas Potensi Utama, 2024)
Internet of Things (IoT) is a technology with great potential to enhance the quality of life through inter-device connectivity. One of the rapidly growing implementations of IoT is the smart home, aimed at creating more efficient, secure, and comfortable living spaces. This community service initiative seeks to improve public understanding and skills related to the application of IoT in smart homes. The training involves students, lecturers, and community members interested in smart home technology. Using a combined approach of theory and practice, participants are trained to design and implement IoT-based solutions, not only for household needs but also for other sectors, such as industry and agriculture. The training equips participants not only with fundamental knowledge about IoT but also with practical skills in using various IoT platforms such as Arduino and Arduino Cloud. Participants are also introduced to various IoT components, including sensors, actuators, and microcontrollers used in smart home systems. By the end of the training, participants are expected to apply IoT technology in their daily lives and develop innovative solutions to create more efficient and secure smart homes. Additionally, the training aims to increase awareness and technological literacy among the community while fostering creativity and the ability to develop IoT applications that can provide long-term benefits for daily life and industrial sectors.